PERMINTAAN PASAR TERHADAP PERUSAHAAN PADA PASAR PERSAINGAN SEMPURNA - Hasrul, Saddam; Andiansyah, Farma (IJMA (Indonesian Journal of Management and Accounting), 2024)
Markets may be the common trading instruments for merchandise and administrations. Market costs are shaped by various variables that at the time shape the demand and supply of products and services. Customer demand is influenced by various variables such as costs, customer salaries, tastes, desires and benefit levels. Meanwhile, producer supply is also influenced by various variables, such as mashlahah, profit, and cost. The interaction between supply and demand that will frame the adjustment point can be altered from either the demand or supply side, either due to organized deviations or unstructured deviations. Idealizing competition exhibitions will be able to provide reasonable costs for dealers and buyers. Therefore, if market instruments are disrupted, cost equity will not be achieved. Islam places the market in an important position in the economy. So the role of the government is very important to encourage the implementation of idealizing the elements of the exhibition such as the regulation of mediation of the acceptance of costs that remain based on equity. Storefront equilibrium in the short run in a perfectly competitive storefront can be a condition where the amount supplied rises to the amount demanded.